Fe(III)/TiO2-Montmorillonite Photocatalyst in Photo-Fenton-Like Degradation of Methylene Blue - Is Fatimah; Iwan Sumarlan; Tuty Alawiyah (International Journal of Chemical Engineering)
A photodegradation process of methylene blue (MB) in aqueous solution using Fe(III)/TiO2-montmorillonite photocatalyst is presented. The photocatalyst material was prepared using Indonesian natural montmorillonite in TiO2 pillarization process followed by Fe(III) ion exchange. Kinetic study on MB degradation was conducted and evaluated by three kinetic models: the pseudo-first- and second-order equations and the Elovich equation. From the results, it is concluded that the degradation under the photo-Fenton-like process utilizing Fe(III)/TiO2-montmorillonite photocatalyst conformed to the Elovich kinetic model.